KEMITRAAN DALAM PENDIDIKAN ANAK USIA DINI (ANALISIS TERHADAP POLA DAN TINGKAH LAKU ANAK USIA DINI DAN LINGKUNGAN) - Hafidzi, Anwar; Putri, Hadisa (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2018)
Abstract: Partnership is a cooperative relationship between several parties in achieving a certain work relationship. The partnership between the school and the family and community in building an educational ecosystem is in line with the Ministry of Education and Culture's vision of